Outcome of Intraoperative Injection versus Sponge-applied Mitomycin C during Trabeculectomy (Journal of National Institute of Ophthalmology, 2026)
Background: Mitomycin C (MMC) is a critical adjuvant to trabeculectomy surgery, traditionally applied by sponge soaking. Intraoperative injection has nonetheless been suggested as a practical delivery method with potential advantages. The present article compares intraoperative injection and sponge-applied MMC for efficacy and safety in trabeculectomy. Methods: This prospective comparative study was conducted at the National Institute of Ophthalmology & Hospital from May 2024 to October 2024, enrolled 80 patients undergoing trabeculectomy, evenly divided into receiving MMC either by intraoperative injection (n=40) or sponge application (n=40). Participants with primary open-angle glaucoma, primary angle-closure glaucoma, or secondary glaucoma were recruited by purposive sampling. The primary outcomes were intraocular pressure control and surgical success at 12 months. The secondary outcomes were immediate, early (3 months), and late complications. Statistical analysis used chi-square tests, Kaplan-Meier survival analysis, and multivariate logistic regression. Results: The results of the injection group were better on a number of parameters. Complete surgical success at 12 months was much higher with injection (75.0% vs 40.0%, p=0.004). Day-1 IOP ≤10 mmHg occurred in 50.0% of injection patients and 20.0% of sponge patients (p=0.008). Early bleb formation was improved with injection (80.0% vs 45.0%, p=0.005). Complications were significantly reduced with the injection technique, e.g., hyphema (2.5% vs 17.5%, p=0.018), shallow anterior chamber (5.0% vs 22.5%, p=0.031), and necessity for needling (5.0% vs 30.0%, p=0.003). Multivariate analysis confirmed injection technique as an independent predictor of surgical success (OR 3.94, 95% CI 1.42-10.94, p=0.008). Conclusion: MMC intraoperative injection was found to be more effective and safer compared to the traditional sponge application in trabeculectomy, with higher success rates and fewer complications. The technique is a valuable innovation for glaucoma surgery with significant clinical implications.J.Natl.Inst.Ophthalmol.2024;7(2): 09-19